Fish sounds and boat noise are prominent soundscape contributors in an urban European estuary - Vieira, Manuel (2021)
Passive acoustic monitoring is a valuable tool for non-intrusive monitoring of marine environments, also allowing the assessment of underwater noise that can negatively affect marine organisms. Here we provide for the first time, an assessment of noise levels and temporal soundscape patterns for a European estuary. We used several eco-acoustics methodologies to characterize the data collected over six weeks within May 2016 - July 2017 from Tagus estuary. Biophony was the major contributor dominated by fish vocalizations and the main driver for seasonal patterns. Maritime traffic was the major source of anthropogenic noise, with daily patterns monitored using 1584 Hz third-octave band level. This indicator avoided biophony and geophony, unlike other indicators proposed for the EU Marine Strategy Framework Directive. Furthermore, the frequency overlap between anthropophony and biophony demands precautionary actions and calls for further research. This study provides an assessment that will be useful for future monitoring and management strategies.